"Cities are Good for Us": Assessment of Urban Attractiveness by Students. Issue 3 (April 2020) - Antonova, N; Abramova, S; Polyakova, V
Abstract: The article reveals the foundation of attractiveness of the city as a place of residence, as a place of realization of needs of student youth. The city, as a high-resource territory, becomes a factor in the formation of migration attitudes of the young generation, which acts as a driver for its successful functioning and development. Cities engage in global competition for human resources. The lack of competitive advantages (such as a favourable environment, high level of income, quality of life, developed infrastructure) is becoming a factor of outflow of youth to more attractive areas. In 2017, we conducted a sociological study of students of the city of Yekaterinburg (Russia). Based on a standardized survey of 200 students (71 men and 129 women), as well as on 8 in-depth interviews with 4 women and 4 men, the article argues that the factors of the city's attractiveness are the conditions contributing to the upward vertical mobility. The most attractive characteristic of the urban environment is the economic, environmental and socio-cultural sustainability, which creates the conditions for the successful implementation of life plans, initiative and innovation. When choosing a city for the realization of their interests, students consider the territory's ability to provide opportunities for informal interaction and free choice of everyday practices. These indicators of attractiveness demonstrate that students claim their right to the city: they change themselves by changing the city.